Cardiac Inflammation, Oxidative Stress, Nrf2 Expression, and Coagulation Events in Mice with Experimental Chronic Kidney Disease. (16th January 2021) - Nemmar, Abderrahim; Al-Salam, Suhail; Beegam, Sumaya; Zaaba, Nur Elena; Yasin, Javed; Hamadi, Naserddine; Ali, Badreldin H.
Abstract : Chronic kidney disease (CKD) is known to be associated with cardiovascular dysfunction. Dietary adenine intake in mice is also known to induce CKD. However, in this experimental model, the mechanisms underlying the cardiotoxicity and coagulation disturbances are not fully understood. Here, we evaluated cardiac inflammation, oxidative stress, DNA damage, and coagulation events in mice with adenine (0.2% w / w in feed for 4 weeks)-induced CKD. Control mice were fed with normal chow for the same duration. Adenine increased water intake, urine output, relative kidney weight, the plasma concentrations of urea and creatinine, and the urinary concentrations of kidney injury molecule-1 and neutrophil gelatinase-associated lipocalin. It also decreased the body weight and creatinine clearance, and caused kidney DNA damage. Renal histological analysis showed tubular dilation and damage and neutrophilic influx. Adenine induced a significant increase in systolic blood pressure and the concentrations of troponin I, tumor necrosis factor- α, and interleukin-1 β in heart homogenates. It also augmented the levels of markers of lipid peroxidation measured by malondialdehyde production and 8-isoprostane, as well as the antioxidants superoxide dismutase and catalase. Immunohistochemical analysis of the hearts showed that adenine increased the expression of nuclear factor erythroid-derived 2-like 2 by cardiomyocytes. It also caused cardiac DNA damage. Moreover, compared with the control group, adenine induced a significant increase in the number of circulating platelet and shortened the thrombotic occlusion time in pial arterioles and venules in vivo, and induced a significant reduction in the prothrombin time and activated partial thromboplastin time. In conclusion, the administration of adenine in mice induced CKD-associated cardiac inflammation, oxidative stress, Nrf2 expression, and DNA damage. It also induced prothrombotic events in vivo . Therefore, this model can be satisfactorily used to study the cardiac pathophysiological events in subjects with CKD and the effect of drug treatment thereon.